2020
DOI: 10.5545/sv-jme.2020.6840
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Heat Partition Testing in the Cutting Zone for Turning AISI 321 Steel

Abstract: This article shows selected results of experimental tests and the results of analytical and numerical modelling of the thermal characteristics of the cutting process. The tests were conducted for the case of the dry turning of austenitic steel AISI 321 with cutting tools with a flat rake face. The research aimed to determine the actual division of thermal fluxes in the zone of contact between the chip and the rake face. As a result of such work, a formula for a new heat partition coefficient and a formula for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Research [25] has also showed that the highest surface roughness is located in the hole at the entry of the drill into the material, compared to the roughness measured in the hole depth center [25]. There also exist other treatment and measure methods ensuring improved surface roughness [28,29] thermal characteristic [30] and reduced delamination [31,32]; however, they have not been used for the treatment of polymer composites yet.…”
Section: Introductionmentioning
confidence: 99%
“…Research [25] has also showed that the highest surface roughness is located in the hole at the entry of the drill into the material, compared to the roughness measured in the hole depth center [25]. There also exist other treatment and measure methods ensuring improved surface roughness [28,29] thermal characteristic [30] and reduced delamination [31,32]; however, they have not been used for the treatment of polymer composites yet.…”
Section: Introductionmentioning
confidence: 99%